(untitled) (Perner’s Contacts, 2023)
The aim of this paper is to experimentally evaluate energy losses during AC and DC charging of battery electric vehicle (BEV) Hyundai Kona electric 64 kWh. DC charging speed of four different types of BEVs was also measured and compared. Overall charging efficiency, round-trip battery efficiency, on-board electronics consumption during charging and on-board battery charger efficiency were calculated. A strong influence of battery temperature on charging speed and efficiency is observed in DC charging. Charging efficiency is calculated as ratio of energy consumed from battery during the trip to energy supplied by AC wallbox or DC charger during subsequent charging to the same battery state of charge level as at the beginning of the trip. Observed overall charging efficiencies of Hyundai Kona were 85 % (AC) and 92,1 % (DC). Calculated battery round-trip efficiency was 97,6 % (AC charging) and 92,7 % (DC charging). Vehicle’s 12 V board net consumes about 0,3 to 1,4 % of total input power during charging. Data was collected from seventeen AC charging events after the test trips on various types of roads in summer and winter and three DC charging events after the test trips on highway in winter.